Parental Involvement and Academic Success: A Comparative Study Across Low, Middle, and High-Income Families in India - Nisha, Nisha; Verma, Shraddha (Journal of Neonatal Surgery, 2025)
This research investigates how parental involvement in children’s education affects academic achievement among different socioeconomic groups in India, focusing on how family income levels—low, middle, and high—influence the way parents engage with their children’s schooling. The research employed a quantitative cross-sectional survey design, utilizing stratified random sampling to gather data from 450 participants across these income strata in Haryana, India. A semi-structured questionnaire, administered through printed copies, online platforms, and face-to-face interviews, collected comprehensive insights into parental involvement practices. Descriptive statistics were used to analyze the collected responses. The demographic profile revealed a diverse sample, evenly distributed across secondary grade levels and encompassing various school types, parental educational backgrounds, income levels, and occupations. Findings indicated a generally high level of parental engagement, particularly in home-based activities: over 82% of parents regularly assisted with homework, over 86% discussed school activities, and nearly 93% encouraged learning beyond school. However, disparities emerged in school-related and external support activities, suggesting the influence of socioeconomic factors. While 74% attended parent-teacher meetings, a notable portion did not, and 68% actively monitored academic progress. Support for additional tuition also showed variations, with financial constraints likely playing a role. In conclusion, the study affirms a strong parental commitment to education in Haryana, India, but critically demonstrates that the nature and extent of this involvement are significantly shaped by socioeconomic status. While home-based support is widespread, engagement in school-related activities and external academic support is more susceptible to financial and logistical limitations. These findings underscore the imperative for educational institutions and policymakers to develop equitable strategies and flexible support mechanisms to address socioeconomic disparities, thereby empowering all families to foster student academic success in a more inclusive educational environment